2022
DOI: 10.1111/1751-2980.13146
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of triple therapy containing berberine hydrochloride, amoxicillin, and rabeprazole in the eradication of Helicobacter pylori

Abstract: Objective To estimate the effectiveness and safety of triple therapy containing berberine, amoxicillin, and rabeprazole in the eradication of Helicobacter pylori (H. pylori). Methods This prospective, randomized controlled, open‐label, noninferiority trial included treatment‐naive patients with H. pylori infection who were randomly allocated at a ratio of 1:1 into the berberine triple therapy group (berberine hydrochloride 300 mg thrice daily, amoxicillin 1 g twice daily, and rabeprazole 10 mg twice daily) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
0
0
0
Order By: Relevance
“…Of these, 759 articles were excluded after the review of titles and abstracts. Finally, 27 studies were included in this meta‐analysis 19–24,27–47 . Seventeen studies were two‐arm RCTs, eight were three‐arm RCTs, and two were four‐arm RCTs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, 759 articles were excluded after the review of titles and abstracts. Finally, 27 studies were included in this meta‐analysis 19–24,27–47 . Seventeen studies were two‐arm RCTs, eight were three‐arm RCTs, and two were four‐arm RCTs.…”
Section: Resultsmentioning
confidence: 99%
“…However, in these meta‐analyses, only a limited number of studies were included, and the effect of different amoxicillin dosing frequency, and the treatment duration were not considered when synthesizing the results. Moreover, studies with vonoprazan‐based quadruple therapy have been published only recently and thus were not included in the currently published meta‐analyses 19–24 . Hence, a comprehensive comparative analyses of the efficacy and safety of VA dual therapy, VAC triple therapy, and vonoprazan‐based bismuth‐containing quadruple therapy (QBQT), and vonoprazan‐based versus PPI‐based therapies with the consideration of amoxicillin dosing frequency and duration of therapy is needed to guide the treatment of patients with H. pylori infection.…”
Section: Introductionmentioning
confidence: 99%
“…However, for salvage therapy (RR=1.20; 95%CI: 0.82-1.75; P= 0.34; I2= 69%), no significant differences were observed between the two groups (Figure 6). References: [39,41,42,44,[46][47][48][49][50][51][52][53][54] P-CAB: potassium-competitive acid blocker; PPI: proton-pump inhibitor; PPA: per-protocol analysis Subgroup analysis based on the country in which the study was conducted: Pooling data from a total of 13 RCTs that assessed eradication rates using a PPA, our analysis revealed significant overall results favoring the P-CAB group over the PPI group (RR=2.02; 95%CI: 1.33-3.08; P= 0.001; I2= 49%). These findings remained consistent when we analyzed the subgroup-specific to Japan (RR=3.33; 95%CI: 1.83-6.06; P< 0.0001; I2= 35%).…”
Section: Results Of Intervention: Eradication Rate Assessed By Ppamentioning
confidence: 99%
“…However, for the other countries included in the study, no significant differences were identified between the two groups (RR=1.35; 95%CI: 0.96-1.90; P= 0.09; I2= 0%) (Figure 7). References: [39,41,42,44,[46][47][48][49][50][51][52][53][54] P-CAB: potassium-competitive acid blocker; PPI: proton-pump inhibitor; PPA: per-protocol analysis…”
Section: Results Of Intervention: Eradication Rate Assessed By Ppamentioning
confidence: 99%
See 1 more Smart Citation